2017
DOI: 10.3892/mmr.2017.7028
|View full text |Cite|
|
Sign up to set email alerts
|

Altered expression of microRNA-98 in IL-1β-induced cartilage degradation and its role in chondrocyte apoptosis

Abstract: Osteoarthritis (OA) is a multifactorial disease characterized by degeneration of the articular cartilage due to genetic and epigenetic components. The pathogenesis of OA is complex and the mechanism of chondrocyte homeostatic regulation remains to be fully elucidated. Previous studies have demonstrated that microRNAs (miRNAs/miR) contribute to cartilage dysfunction. However, the functional role of miR-98 in interleukin-1β (IL-1β)-induced chondrocyte apoptosis in OA cartilage remains to be investigated. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…MiR-98 expression is decreased in OA chondrocytes, and its inhibition can result in chondrocyte apoptosis; therefore, miR-98 may be applied in targeted OA therapy [ 32 , 33 ]. By enhancing extracellular signal-regulated kinase expression and inhibiting CASP3 , FAS , and Fas ligand expression, recombinant human lactoferrin can reverse dexamethasone-induced chondrocyte apoptosis in OA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-98 expression is decreased in OA chondrocytes, and its inhibition can result in chondrocyte apoptosis; therefore, miR-98 may be applied in targeted OA therapy [ 32 , 33 ]. By enhancing extracellular signal-regulated kinase expression and inhibiting CASP3 , FAS , and Fas ligand expression, recombinant human lactoferrin can reverse dexamethasone-induced chondrocyte apoptosis in OA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-98 inhibited cell apoptosis, whereas HEY2 promoted the apoptosis of hippocampal neurons. A previous study indicated that miR-98 inhibited interleukin-1β-induced cell apoptosis by regulating the expression of Bcl-2 ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The medium was supplemented with 100 U/ml and penicillin/streptomycin. As previously described [ 25 27 ], recombinant IL-1β (R&D Systems) (10 ng/ml) was used to induce cartilage injury for 48 h. Experiments were performed independently for at least 3 times.…”
Section: Methodsmentioning
confidence: 99%